Two new species of the genus Prosopistoma (Ephemeroptera: Prosopistomatidae) from Iraq and Algeria - Bojková, Jindřiška; Soldán, Tomáš (Zootaxa, 2015)
In addition to the three so far known species of Prosopistoma Latreille, 1833 from West Palaearctic region, P. pennigerum (Müller, 1785), P. oronti Alouf, 1977 and P. orhanelicum Dalkıran, 2009, two new species are described based on larvae. Prosopistoma helenae sp. n. has been found in Iraq (Tigris River in Mosul) and Prosopistoma alaini sp. n. in Algeria (Oued Isser, Sidi Abdelli). Critical distinguishing characters of all West-Palaearctic species of Prosopistoma are discussed in detail.